Eating right in the Renaissance - Albala, Ken, 1964- (Berkeley : University of California Press, 2002)
Eating right has been an obsession for longer than we think. Renaissance Europe had its own flourishing tradition of dietary advice. Then, as now, an industry of experts churned out diet books for an eager and concerned public. Providing a cornucopia of i.
Cover -- Contents -- Acknowledgments -- Note on Spelling -- Introduction -- 1. Overview of the Genre -- 2. The Human Body: Humors, Digestion, and the Physiology of Nutrition -- 3. Food: Qualities, Substance, and Virtues -- 4. External Factors -- 5. Food and the Individual -- 6. Food and Class -- 7. Food and Nation -- 8. Medicine and Cuisine -- Postscript: The End of a Genre and Its Legacy -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Illustrations.
Includes bibliographical references (pages 295-308) and index.
Print version record.
JSTOR
Keywords: Gastronomy; Food habits -- Europe -- History; Food habits; Europe; Diet Therapy -- history; Diet -- history; Feeding Behavior; Socioeconomic Factors; Europe; Gastronomie; Habitudes alimentaires -- Europe -- Histoire; Habitudes alimentaires; Europe; gastronomy; COOKING -- General; HISTORY -- Renaissance; Food habits; Gastronomy; Europe; Dieetleer; Eetcultuur; Europa (geografie); History